(untitled) (Ameghiniana, 2013)
A new species of palm stem and its rootlets, from the Salamanca Formation (Danian) in the Cerro Abigarrado, Chubut Province, is described. The species is characterized by 1) the presence of two metaxylematic vessels in the fibrovascular bundles of the stem, which have oblique plates with scalariform perforations; 2) fibrous bundles in the parenchyma of the stem but absent in the root cortex; 3) root with medulla; 4) sphaerical and conical stegmata; 5) outer fibrovascular bundles with reduced fibrose sheath; 6) columnar habito Comparison with P. cbeyenense Stevens (1921) and P. surangei Lakhanpal (1955) and with other Palmoxylon are made. From the studies on recent palms, it is concluded that P. patagonicum has intermediate characters with the subfamilies Sabaloideae, Cocoideae and Bac- trioideae, which are now representad in Chile and Argentina. On this ground it is suggested that P. patagonicum might belong to the ancestral stock from which these subfamilies evolved. Finally some paleoclimatic implications are discussed; it is suggested that in Central Patagonia, during the Danian, the climate was temperate or perhaps subtropical.